A Systematic Literature Review of The Bronchiectasis - Anugrah, Yunan Prabu Jaya; Hasanah, Mielosita; Mikailla, Romy Healthy; Nitzana, Lale Nubya; Ilmiah, Janiya Abdila (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Bronchiectasis is a chronic respiratory condition marked by irreversible dilation of the bronchi, leading to persistent cough and excessive sputum production. This study aims to describe the pathophysiology, clinical features, diagnosis, and management strategies of bronchiectasis, with emphasis on current approaches relevant to the Indonesian context. A narrative literature review was conducted using national and international sources. Key clinical and radiological findings, treatment modalities, and prognosis indicators were summarized, with reference to validated scoring systems such as FACED and Bronchiectasis Severity Index (BSI). Bronchiectasis is most prevalent among women and the elderly. Common etiologies include post-infectious lung disease, cystic fibrosis, and chronic inflammation. HRCT is the gold standard for diagnosis. Management focuses on airway clearance, antibiotic therapy, and reducing exacerbations. Prognosis varies depending on severity, but early and personalized treatment improves outcomes. Bronchiectasis remains under-recognized in Indonesia, despite its significant burden. Timely diagnosis using HRCT and targeted therapy can improve patient quality of life and reduce complications. Efforts should be made to increase clinical awareness, improve diagnostic access, and promote preventive measures such as immunization, smoking cessation, and early treatment of respiratory infections.